Pemberdayaan Usaha Laundry dalam Meningkatkan Kualitas Pelayanan dan Pengelolaan Keuangan di Kelurahan Pasuruan - Lestari, Sri; Hayati, Cucu; Sanggarwati, Diah Ayu (Jurnal Ekonomi, Pendidikan dan Pengabdian Masyarakat, 2024)
Empowerment of laundry businesses in Pasuruan Village aims to improve the quality of service and financial management for local business actors. This research explores the impact of an empowerment program involving skills training, financial management workshops, and strategies for improving service quality. The methods used include direct training, individual consultations, and periodic evaluations. The research results showed that program participants experienced significant improvements in operational and managerial skills. The quality of laundry business services has increased, marked by improvements in customer satisfaction and operational standards. Apart from that, financial management also showed improvement, with improvements in financial planning and better transaction recording. This program was also successful in identifying several challenges faced, such as limited resources and the need for ongoing assistance. Based on these findings, it is recommended that the empowerment program be continued with an emphasis on continued assistance and strengthening local business networks.